Biotechnology and Sustainable Development: Voices of the South and North 2003
DOI: 10.1079/9780851996752.0191
|View full text |Cite
|
Sign up to set email alerts
|

Globalization and access to biotechnology-derived health care products: a view from Egypt.

Abstract: This chapter reviews the use of biotechnology in developing drugs and foods with health claims, and some safety and ethical considerations. The role of bioinformatics, pharmacogenomics, proteomics, nanotechnology approaches, molecular modelling, customized medicine and pharming industry in drug development is described. The impact of globalization and cost of developing biotechnology-derived health care products on affordability and access of these products in Egypt is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As biosimilars continue to enter the Egyptian pharmaceutical market, they not only offer huge cost savings for patients, physicians, insurance providers, and governments, but also add to the physician's list of treatments available for a variety of diseases. 9,10 Several studies have concluded that biosimilar epoetin-α is the most cost-effective erythropoiesisstimulating agent available for managing chemotherapyinduced anemia using both fixed and weight-based dosing strategies. Using fixed-dosing scenarios, the average cost savings associated with use of biosimilar epoetin-α 40,000 IU ranged from €990 (13.8%) to €3,042 (33.0%), while for biosimilar epoetin-α 30,000 IU the average savings ranged from €2,534 (35.4%) to €4,587 (49.7%).…”
Section: Biosimilars 10 May 2014 Number Of Times This Article Has Beementioning
confidence: 99%
“…As biosimilars continue to enter the Egyptian pharmaceutical market, they not only offer huge cost savings for patients, physicians, insurance providers, and governments, but also add to the physician's list of treatments available for a variety of diseases. 9,10 Several studies have concluded that biosimilar epoetin-α is the most cost-effective erythropoiesisstimulating agent available for managing chemotherapyinduced anemia using both fixed and weight-based dosing strategies. Using fixed-dosing scenarios, the average cost savings associated with use of biosimilar epoetin-α 40,000 IU ranged from €990 (13.8%) to €3,042 (33.0%), while for biosimilar epoetin-α 30,000 IU the average savings ranged from €2,534 (35.4%) to €4,587 (49.7%).…”
Section: Biosimilars 10 May 2014 Number Of Times This Article Has Beementioning
confidence: 99%